The nineteenth century methodological roots of the Western pharmaceutical industry: A historical perspective - Conti, Andrea Alberto (Acta Biomedica Atenei Parmensis, 2024)
The evolution of the pharmaceutical industry is a captivating journey through time. A number of factors have contributed to its birth, both at the cultural-academic, scientific-technical and social-environmental levels. Its historical roots are fascinating and four subsequent major pharmaceutical traditions may be acknowledged in the Western world.The Mittel-European line involves countries such as Germany and Switzerland, in which the pharmaceutical tradition derives directly from the existing chemical industry; it emerges in the eighteen hundreds with a typical industrial dimension. The Mediterranean strand originates in Italy and in France. Here the pharmaceutical industry arises from family-based pharmaceutical laboratories that in the course of the nineteenth century flank and then replace the grocers' shops of the Middle Ages.The British pharmaceutical tradition is characterized by UK entrepreneurs who begin producing drugs in the first half of the eighteen hundreds, as also by “foreign” manufacturers who adopt an articulated proactive marketing to sell medicines in Great Britain and in the British colonies.The fourth Western tradition is collocated in the USA, where some nineteenth century pharmaceutical companies were targeted to the elaboration and the marketing of already available drugs, while others began to develop new drugs to sell to physicians and pharmacists.The recent COVID-19 pandemic has clearly highlighted the strategic role of the pharmaceutical industry in ensuring access to and appropriate use of effective, safe and reliable medical products and related services, including vaccines, so as to improve human health.